2017
DOI: 10.1186/s13075-017-1487-6
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 promotes MMP-3 production via the CX3CR1, c-Raf, MEK, ERK, and NF-κB signaling pathway in osteoarthritis synovial fibroblasts

Abstract: BackgroundOsteoarthritis (OA) is a degenerative joint disease that affects the cartilage, synovium, and subchondral bone and is the leading cause of disability in older populations. Specific diagnostic biomarkers are lacking; hence, treatment options for OA are limited. Synovial inflammation is very common in OA joints and has been associated with both OA’s symptoms and pathogenesis. Confirming the role of the synovium in OA pathogenesis is a promising strategy for mitigating the symptoms and progression of OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 41 publications
0
67
1
Order By: Relevance
“…The study showed that CCL4 and CCL4L2 expressions were involved in the canonical NF-κB signaling pathway. Hou et al discovered increased expression of CX3CL1 in synovial fibroblasts from patients with osteoarthritis [9]. CX3CL1 induced MMP-3 expression in a time-dependent and dose-dependent manner by reacting with its receptor, CX3CR1 [9].…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 99%
See 3 more Smart Citations
“…The study showed that CCL4 and CCL4L2 expressions were involved in the canonical NF-κB signaling pathway. Hou et al discovered increased expression of CX3CL1 in synovial fibroblasts from patients with osteoarthritis [9]. CX3CL1 induced MMP-3 expression in a time-dependent and dose-dependent manner by reacting with its receptor, CX3CR1 [9].…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 99%
“…Hou et al discovered increased expression of CX3CL1 in synovial fibroblasts from patients with osteoarthritis [9]. CX3CL1 induced MMP-3 expression in a time-dependent and dose-dependent manner by reacting with its receptor, CX3CR1 [9]. Furthermore, Alaaeddine et al showed enhanced expression of CCL20 and its receptor, CCR6, in cartilages compared to controls.…”
Section: The Role Of Chemokines In Osteoarthritismentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in patients with PE induced MMPs production is associated with endothelial dysfunction as a result of inadequate cell invasiveness, 3,7 as well as different inflammatory cytokines (IL-1β, TNFα), and chemokines production. 18,19 Our results indicate that the ratio of the act/proMMP isoforms in patients with severe PE is found mainly at actMMP with respect to healthy pregnant patients. This suggests that the regulatory system of MMPs is modified in the endothelial microenvironment of patients with severe PE.…”
Section: Discussionmentioning
confidence: 65%